Relationship between nutritional status and mandibular length in subjects aged 10-16 years - Hilda Fitria Lubis; Rachel Tiong (Wolters Kluwer Medknow Publications, 2021)
Background: Malocclusion is a significant dental health problem in Indonesia. Malocclusion has multifactorial causes, including nutrition. Malnutrition may have an adverse effect on mandibular length and lead to tooth malposition. Objective: The aim of this article is to investigate the relationship between nutritional status and mandibular length in subjects aged 10-16 years. Methods: This was an observational analytic study with a cross-sectional design. The sampling method was purposive sampling. The subjects were 100 children (50 children with normal nutrition and 50 children with nutrition lower than normal) aged 10-16 years from Al-Ikhlas Islamic Elementary School and Advent 2 School in Medan, with no history of orthodontic treatment and facial trauma and not wearing prostheses. All the subjects were photographed with their heads held in a natural position. The photographs were analyzed using a computer program CorelDraw X7 to measure the length of the mandible. All statistical analyses were performed using SPSS. Univariate analyses were performed to obtain the mean and standard deviation (SD) values of all parameters. Descriptive statistics were obtained, and data were tested for normality using the Kolmogorov-Smirnov test for distribution. Variables that conformed to a normal distribution were analyzed using unpaired t-tests. Results: The mean mandibular length in those with nutritional status lower than normal was 94.52 ± 5.89 mm, whereas it was 109.44 ± 4.85 mm in those with normal nutritional status. The results of an unpaired t-test (P = 0.001) revealed that there was a difference of mandibular length between subjects with normal nutrition status and lower than normal nutrition status. Conclusion: There was a relationship between nutritional status and mandibular length in subjects aged 10-16 years.